Non Operative Management of Splenic Trauma - Reanpinyawat, Chairat (Journal of Health Science of Thailand, 2018)
The prospective study was carried out on thirtyfive splenic trauma patients who were treated in Chai Nat general hospital during two-year period from January 1, 2006 to December 31, 2007. Sixteen of these patients had early emergency operation for splenectomy and nineteen patients with stable vital sign underwent initially management by observation without operation, one of the nineteen nonoperative management patients, who failed observative management, required splenectomy. There were no significant difference in length of hospital station, units of blood transfusion between operative and nonoperative groups (p > 0.05). No mortality was reported in both groups. In conclusion, nonoperative management in splenic trauma is an attractive alternative in a selective group of patients.